Preservice Training Amid a Pandemic in Ghana: Predictors of Online Learning Success Among Teachers - Nketsia, William; Opoku, Maxwell P.; Mohamed, Ahmed H.; Kumi, Emmanuel O.; Twum, Rosemary; Kyere, Eunice A. (Frontiers in Education, 2021)
The coronavirus disease 2019 outbreak has brought the world to a standstill, especially the education sector. Globally, it has claimed over two million lives, with over 100 million people infected, forcing schools to close down. This has reignited the importance of online teaching and learning for preservice teachers who comprise the next frontiers in providing online education to their future students. However, studies on online learning [OL] success among preservice teachers in developing countries, such as Ghana, remain scarce. Accordingly, this study mainly aimed to assess the predictors of OL success among preservice teachers in Ghana. Bandura’s social cognitive theory guided the study; in total, 526 preservice teachers were recruited from four colleges of education. Although the teachers were ambivalent regarding the success of OL, significant differences were found between the following demographics: gender, specialization, marital status, the preferred mode of learning, and the place of residence. Moreover, the study discussed the need for intensive information and communications technology education among preservice teachers, particularly women, developing their confidence in computer skills, and other recommendations.